2007
DOI: 10.1037/1053-0797.17.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Dreams of female university students: Content analysis and the relationship to discovery via the Ullman method.

Abstract: This study extended the research on the dreams of students by examining the actual content of female students' dreams and to what extent the content related to discovery via the Ullman method. Further analyses were conducted to examine what content categories significantly predicted discovery. Participants were 56 female undergraduate students who provided a dream and participated in the Ullman method of group interpretation. Dream content was analyzed via the Hall and Van de Castle method of content analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 12 publications
6
39
1
Order By: Relevance
“…Seventh, the present study was primarily quantitative; dream contents were not assessed. However, the present approach has some merit in counterbalancing previous studies focusing predominantly on qualitative aspects of adolescents' dreams [17][18][19][20]. Finally, expert ratings, which might have counterbalanced possible self-rating biases, were not obtained, which further limits the validity of the present pattern of results.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Seventh, the present study was primarily quantitative; dream contents were not assessed. However, the present approach has some merit in counterbalancing previous studies focusing predominantly on qualitative aspects of adolescents' dreams [17][18][19][20]. Finally, expert ratings, which might have counterbalanced possible self-rating biases, were not obtained, which further limits the validity of the present pattern of results.…”
Section: Discussioncontrasting
confidence: 65%
“…For example, Nielsen et al [19] investigated dream contents in a sample of 1,348 Canadian students and found that, independent of adolescents' gender, dreams contained the following five prevalent themes: being chased; sexual experiences; falling; school, teachers, and studying; and arriving late. Importantly, these results were replicated by the study performed by King and DeCicco [20], which lends support to the continuity hypothesis (cf. [3]) in that the prevalent themes seemed to reflect everyday concerns related to school and psychosexual development.…”
supporting
confidence: 85%
“…Within the field of dream research, there appears to be a growing consensus among researchers that lived experiences such as playing sports (Erlacher & Schredl, 2004;Meyers, Cooke, Cullen & Liles, 1979), being single or partnered (Schredl, 2001), divorced (Cartwright, Lloyd, Knight, & Trenholme, 1984), male or female (Schredl & Piel, 2005;Schredl, Sahin, & Schafer, 1998), a college student (DeCicco, 2007;Domhoff, Meyer-Gomes, & Schredl, 2005-2006Nielsen, Zadra, Simard, Saucier, Stenstrom, Smith et al, 2003), or preparing for an examination (Schredl, Pallmer, & Montasser, 1996) influence an individual's dream content. These studies provide support for the "continuity hypothesis" (for an overview see Domhoff, 1996;Strauch & Meier, 1996) that an individual's dreams are a reflection of their waking life concerns, interests, behavior, and emotional preoccupations.…”
mentioning
confidence: 99%
“…More contemporary work has produced a very wide range of books and writings on dream interpretation techniques (For examples see: Barcaro, 2010;DeCicco, 2009;Delaney, 1993). Recent studies have shown that dream interpretation connects dream imagery to the dreamer's life in relevant and meaningful ways (DeCicco, Lyons, Panier & Wright, 2010;DeCicco, 2009;2007a;2007b;DeCicco & Higgins, 2009;Goelitz, 2001;Wadensten, 2009). For example, it has been found that recovering alcoholics find meaning in their dream imagery related to their addiction, to their recovery, and to past events directly relating to their addiction (DeCicco & Higgins, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been found that recovering alcoholics find meaning in their dream imagery related to their addiction, to their recovery, and to past events directly relating to their addiction (DeCicco & Higgins, 2009). University students report dream meaning to be related to school, romantic relationships, and to their emotions in relation to these two factors (DeCicco, 2007a;2007b;Clarke, DeCicco, & Navara, 2010). Similarly, cancer patients find meaning in their illness and in waking day concerns via dream interpretation (DeCicco, Lyons, Pannier & Wright, 2010;Cannici, Malcolm & Peek, 1983;Davidson, Feldman-Stewart, Brennenstuhl & Ram, 2007;Davidson, MacLean, Brundage & Schulze, 2002;Horton, 1998;Ward, Beck, Roscoe, 1961).…”
Section: Introductionmentioning
confidence: 99%